Are serum autoantibodies associated with brain changes in systemic lupus erythematosus? MRI data from the Leiden NP-SLE cohort. (January 2019) - Magro-Checa, C.; Kumar, S.; Ramiro, S.; Beaart-van de Voorde, L.J.; Eikenboom, J.; Ronen, I.; de Bresser, J; van Buchem, M.A; Huizinga, T.W.; Steup-Beekman, G.M.
Objective: The effect of serum autoantibodies on the brain of systemic lupus erythematosus (SLE) patients remains unclear. We investigated whether serum autoantibodies, individually and assessed in groups, are associated with specific brain-MRI abnormalities or whether these structural changes are associated with other SLE-related or traditional cardiovascular disease risk factors. Methods: All patients underwent brain 3Tesla-MRI. White matter hyperintensities (WMHs), ischemic lesions, inflammatory-like lesions and cerebral atrophy were scored. Serum autoantibodies analyzed included lupus anticoagulant (LAC), anticardiolipine (aCL) IgG and IgM (first 3 also grouped into antiphospholipid autoantibodies (aPL)), anti-dsDNA, anti-SSA, anti-SSB, anti-RNP, and anti-Sm (the latter 5 grouped into SLE-related autoantibodies). Associations were assessed using logistic regression analysis adjusted for potential confounders. Furthermore, a sensitivity analysis including anti-Beta2 glycoprotein-1 antibodies (anti-β2GP1) in the aPL group was performed and the potential modification role of the neuropsychiatric clinical status in the model was assessed. Results: 325 patients (mean age 42 years (SD 14), 89% female) were included. The following MRI-brain abnormalities were found: WMHs (71%), lacunar infarcts (21%), gliosis (11%), micro-hemorrhages (5%), large hemorrhages (2%), inflammatory-like lesions (6%) and atrophy (14%). No associations were found between individual or total SLE-related autoantibodies and inflammatory-like lesions. A higher number of positive aPL was associated with lacunar infarcts (OR 1.37 (95%CI 1.02–1.99) and gliosis (OR 2.15 (1.37–3.37)). LAC was associated with lacunar infarcts in white matter (OR 3.38 (1.32–8.68)) and atrophy (OR 2.49 (1.01–6.15)), and aCL IgG with gliosis (OR 2.71 (1.05–7.02)). Among other variables, SLE patients with hypertension presented a higher chance for WMHs (OR 5.61 (2.52–12.48)) and lacunar infarcts in WM (OR 2.52 (1.10–5.74)) and basal ganglia (OR 8.34 (2.19–31.70)), while cumulative SLE-damage was correlated with lacunar infarcts in WM (OR 1.43 (1.07–1.90)), basal ganglia (OR 1.72 (1.18–2.51)) and cerebellum (OR 1.79 (1.33–2.41)). These associations were confirmed in the sensitivity analysis. Conclusions: Brain abnormalities in SLE represent different underlying pathogenic mechanisms. aPL are associated with ischemic brain changes in SLE, while the presence of SLE-related serum autoantibodies is not related to inflammatory-like lesions. Hypertension and cumulative SLE-damage associate with ischemic MRI-brain changes in SLE, suggesting the importance of accelerated atherosclerosis in this process.